2017
DOI: 10.1155/2017/4391587
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Time Delay in Perceptual Decision-Making: Neuronal Population Modeling Approach

Abstract: Impairments in decision-making are frequently observed in neurodegenerative diseases, but the mechanisms underlying such pathologies remain elusive. In this work, we study, on the basis of novel time-delayed neuronal population model, if the delay in self-inhibition terms can explain those impairments. Analysis of proposed system reveals that there can be up to three positive steady states, with the one having the lowest neuronal activity being always locally stable in nondelayed case. We show, however, that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…We model these delays through Delayed Differential Equations (DDEs). DDEs are often used to model biological systems [20, 32, 4754] because they exhibit a rich dynamical repertoire, and in particular, they fall into oscillatory regime on the edge of instability. DDEs were also used in the neural mass and neural field models of cortical activity [5559].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We model these delays through Delayed Differential Equations (DDEs). DDEs are often used to model biological systems [20, 32, 4754] because they exhibit a rich dynamical repertoire, and in particular, they fall into oscillatory regime on the edge of instability. DDEs were also used in the neural mass and neural field models of cortical activity [5559].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we investigate a winner-take-all population model with delayed local inhibition to characterize perceptual switches in the binary decision making. We have proposed this model in our previous work [20]. In this work, we investigated mathematical properties of this model, especially with respect to the influence of the value of inhibitory delays on the emergence of temporal switches in the decision making.…”
Section: Introductionmentioning
confidence: 99%
“…But how do the oscillations 48 arise? Some hint was given by Deco et al [13] who demonstrated in a simulation study that 49 a network of nodes with sigmoidal transfer functions, coupled with transmission delays, can 50 start oscillating in the gamma range when tuned to a subcritical state.…”
mentioning
confidence: 99%
“…DDEs are often used to model biological systems [27,[41][42][43][44][45][46][47][48][49] because they exhibit a rich 311 dynamical repertoire, and in particular, they fall into oscillatory regime on the edge of instability. 312 DDEs were also used in the neural mass and neural field models of cortical activity [50][51][52][53][54].…”
mentioning
confidence: 99%